Intrarater reliability of pain intensity, tissue blood flow, thermal pain threshold, pressure pain threshold and lumbo-pelvic stability tests in subjects with low back pain - Aatit Paungmali (2018)
Purpose: This preliminary study aimed to determine the intrarater reliability of the quantitative tests for the study of non-specific low back pain. Methods: Test-retest reliability of the measurements of ratio data was determined by an intraclass correlation coefficient (ICC), standard error of measurements (SEMs), coefficient of variation (CV), and one-way repeated measures ANOVA using the values collected from 13 young individuals (25.8 ± 6.2 years) with chronic non-specific low back pain on two occasions separated by 2 days. Percent agreement of the ordinal data was also determined by Cohen's Kappa statistics (kappa). The measures consisted of tissue blood flow (BF), average pain visual analog scales (VAS), pressure pain threshold (PPT), cold pain threshold (CPT), heat pain threshold (HPT) and lumbo-pelvic stability test (LPST). An acceptable reliability was determined as the ICC values of greater than 0.85, SEMs less than 5%, CV less than 15%, the kappa scores of greater than 80% and no evidence of systematic error (ANOVA, P > 0.05). Results: ICC of all measures in the lumbo-sacral area were greater than 0.87. The kappa was also greater than 83%. Most measures demonstrated a minimal error of measurements and less potential of systemic error in nature. Only the SEMs and the CV of the CPT exceeded the acceptable level. Conclusions: It is concluded that most of the quantitative measurements are reliable for the study of non-specific low back pain, however the CPT should be applied with care as it has a great variation among individuals and potential of measurement error. © 2012 by Sports Medicine Research Center, Tehran University of Medical Sciences.